An inscribed Hero Stone near the Shiva Temple in Morkhana village - Temples of India Project Team (Jio Institute, 2024)
An inscribed hero stone in a row of such steles near the Shiva Temple in Morkhana village. The stele is partially broken and survived with a depiction of a male figure mounted on a horse. Below the depiction is a three-line inscription. It is not entirely legible but the date of Vikaram Samvat 15__ can be deduced from it. The mounted horse is in a marching position. The stele is approximately a foot in height.